“How Do You Know Who You Are?”: Marjorie Prime on Envisioning Humanity Through the Faculty of AI-Powered Memory as Reconstructive Tissue - Bendrat, Anna (Text Matters: A Journal of Literature, Theory and Culture, 2023)
In reference to the theme of the issue devoted to literary extremities, Jordan Harrison’s play Marjorie Prime raises thought-provoking questions about the potential benefits and drawbacks of advanced AI technology by exploring the nature of memory, identity, and mortality, as well as the ethical implications of creating artificial intelligence that can mimic human behavior and emotions. This article argues that the play positions its AI character—a computerized hologram of Marjorie’s late husband Walter—at the intersection of two divergent perspectives on memory reactivation enhanced by AI-powered technology. While, on the one hand, the humanoid is seen as a potent tool which helps to reduce the cognitive impairment caused by dementia, on the other hand, there is a concern that technological interventions may trigger episodic memory change, testifying to the plastic, and thus reconstructive, character of this foundational human faculty. The article seeks to negotiate the interplay of benefits and dangers of technology-assisted memory reactivation by exploring two divergent ideas represented by Marjorie’s daughter Tess and her son-in-law Jon regarding what would comfort their mother, and, ultimately, their differing ways of comforting each other and themselves individually as the carers of an elderly person. In analyzing how creative and destructive forces exhibited by AI-powered digital tools cross-inhabit the declining memory inflicted by dementia, the article unpacks both the vast potential and the limits of technology while attempting to answer uncomfortable questions about the essence of human existence posed by aging and dementia.